Recruitment and Selection Educators at Mulawarman University Samarinda East Kalimantan - Sutikno Sutikno; Suryono Agus; Endah Setyowati (Sekolah Pascasarjana Universitas Brawijaya, 2020)
The purpose of this research is to describe and analyze the recruitment and selection of teaching staff at Mulawarman University to realize good governance so that they can compete nationally and internationally towards World Class University and face the challenges of the Industrial Revolution 4.0, and are required to master three literacy fields, namely literacy in technology, humanities and artificial intelligence (AI). So universities must be able to have human resources, especially educators who are professional and have international standards. The success in getting professional educators lies in recruitment, selection, training, and development. The problem that arises is that in the recruitment of educators, state universities always get less formation than is needed, while the ratio of lecturers and students must be met. The series of decision making regarding the appointment of contract lecturers carried out by Mulawarman University to meet the ratio of lecturers to students needs to be examined and explored further. The research method used is qualitative, using data collection techniques from interviews, observation and documentation studies as well as using qualitative data analysis of the Spradley model. The findings in the field show that there are two series of recruitment and selection activities, the first is the recruitment and selection for CPNS educators, and the second is for Non-PNS educators through several stages.